Use of ecological modelling in animal studies (Zoological Records and Reviews, 2025)
Ecological modelling -- the mathematical and computational representation of ecological processes, populationdynamics, and species-environment relationships -- has become an indispensable analytical framework in animalecology, enabling the integration of empirical data with mechanistic theory to generate predictions, test hypotheses, andsupport conservation management decisions at spatial and temporal scales beyond direct observation. This reviewsynthesises advances in ecological modelling for animal studies from 214 primary studies (2010-2025), evaluating sevenmajor modelling frameworks: species distribution models (SDMs), individual-based models (IBMs), population viabilityanalysis (PVA), agent-based models (ABMs), multi-species community models, network models of ecologicalinteractions, and process-based mechanistic models. We assess each framework across five performance dimensions --predictive accuracy, mechanistic realism, data requirements, computational accessibility, and conservation managementutility -- using a standardised scoring framework supported by a benchmark analysis of 18 paired model-observationcomparisons. Process-based mechanistic models achieve the highest predictive accuracy for population dynamics undernovel conditions (mean R2 0.74 vs. 0.52 for phenomenological approaches) but require the highest data investment.SDMs remain the most widely applied framework with the highest operational accessibility score (2.8/3.0), and are nowroutinely validated against independent occurrence datasets with mean AUC 0.82 for European vertebrates.Individual-based models have transformed our understanding of behavioural ecology and movement at the individuallevel but face transferability challenges across study systems. Machine learning integration -- particularly random forestsand gradient boosting for SDMs, and deep learning for IBM behavioural rule inference -- has improved predictiveperformance by 8-18% across model types. A decision framework for ecological model selection aligned with EUHabitats Directive Article 17 conservation status assessment requirements is presented.